Work-Family Conflict, Psychological Empowerment, and Turnover Intentions among Married Female Doctors (Bangladesh Journal of Medical Science, 2021)
Objective: The aim of the present study was to examine work-family conflict and psychological empowerment as correlates and predictors of turnover intentions among married female doctors. It further aimed to identify significant differences in study variables among the sample in terms of the type of family system i.e., nuclear and joint.Materials and Methods: This correlational study analyzed a sample of 105 married female doctors aged 23-45 years (Mage=31.69; SD=5.20) working in different hospitals of Lahore, Pakistan. Participants completed Work-Family Conflict Scale, Psychological Empowerment Instrument and Turnover Intention Scale.Results and Discussion: Dimensions of work-family conflict had a significant positive relationship with turnover intentions. Furthermore, psychological empowerment had a significant negative relation with turnover intentions. Behavior-based family interference with work and psychological empowerment emerged as significant predictors of turnover intentions among the sample. No significant differences were found in study variables in terms of nuclear and joint family system.Conclusion: Implications of findings are discussed with reference to the medical profession.Bangladesh Journal of Medical Science Vol.20(4) 2021 p.855-863